Cross‐sectional study of in‐vehicle exposure to ultrafine particles and black carbon inside Lebanese taxicabs. (22nd June 2020) - Hachem, Melissa; Bensefa‐Colas, Lynda; Lahoud, Nathalie; Akel, Marwan; Momas, Isabelle; Saleh, Nadine
Abstract: Taxi drivers' exposure to traffic‐related air pollutants inside their vehicles has been reported in different countries but not yet in Lebanon. Thus, we conducted a cross‐sectional study on 20 Lebanese taxi drivers to (1) assess their exposure to ultrafine particles (UFP) and black carbon (BC) inside their vehicles and (2) identify determinants of this exposure. UFP and BC were measured using Diffusion Size Classifier Miniature ® and microAeth ® Model AE51, respectively, for 5 hours. Data on characteristics of vehicles and trips were collected by face‐to‐face interviews. Associations between pollutant levels and their determinants were analyzed by multiple linear regression. The mean of UFP count (35.2 ± 17.6 x 10 3 particles cm ‐3 ) and BC (5.2 ± 1.9 μg m ‐3 ) concentrations in‐taxis was higher in the morning measurements compared with those in the afternoon measurements. UFP count increased in‐taxis by 60% for every 10 minutes spent in blocked traffic and by 84% starting from two trips with smokers compared to trips without smokers. Conversely, UFP count decreased by 30% for every 10 minutes under both air‐conditioning and air recirculation mode with windows closed. BC was not affected by any of these factors. Our findings suggest easy ways to reduce UFP exposure inside vehicles for all commuters.